STOSUNKI PRAWNE MIĘDZY INSTYTUCJĄ UBEZPIECZENIA ZDROWOTNEGO A ŚWIADCZENIODAWCAMI W NIEMCZECH I W POLSCE - Lach, Daniel Eryk (Wydział Prawa i Administracji UAM, 2005)
The author describes the regulations of the process of buying services which are guaranteed to the insured parties. This is a very important issue from the point of view of the very concept of health service which seeks to ensure adequate treatment to those who are eligible to receive it, and which (this being a characteristic of a health insurance model) can only be provided by qualified, professional providers of the services. Consequently, there are three subjects active in the process: the insured, the insurance institution and the medical doctor. Such a situation requires a complicated system of buying medical services. This is a group of issues related to the admission of doctors and hospitals to the system, allowing them to participate in it and negotiate the conditions and contracts, as well as a control exercised over the providers of the said services, making sure that the financial resources are effectively and properly utilised. In the author’s opinion the German experience is a good starting position from which Polish solutions of these problems could develop, as proper solutions are necessary for the stability of a comprehensive health insurance system.
LEGAL RELATIONS BETWEEN A HEALTH INSURANCE INSTITUTION AND THE PROVIDERS OF HEALTH CARE SERVICES IN GERMANY AND POLAND